1998
DOI: 10.1093/oxfordjournals.molbev.a025929
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic profiles: a graphical method for detecting genetic recombinations in homologous sequences

Abstract: Phylogenetic profiles constitute a novel way of graphically displaying the coherence of the sequence relationships over the entire length of a set of aligned homologous sequences. Using a sliding-window technique, this method determines the pairwise distances of all sequences in the windows and evaluates, for each sequence, the degree to which the patterns of distances in these regions agree. This method is suited for exploring data consistency as well as detecting recombinant sequences. A computer program imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(171 citation statements)
references
References 25 publications
3
164
0
4
Order By: Relevance
“…Mapping of the aligned sequences for break points indicative of recombination with the multiple applications available in RDP-V2 Beta 08 (Martin et al, 2005) and PhylPro version 0.8.1.0 (Weiller, 1998) (each at the default settings) resulted in a similar result for all types of analyses. CHIMAERA (Posada & Crandall, 2001), GENECONV (Sawyer, 1989), MAXCHI (Smith, 1992), RDP (Martin et al, 2005) and PhylPro consistently identified fragments of approximately 1768 nt, between nucleotide coordinates 253 and 2020 (fragment I), and between coordinates 2021 and 2742, about 522 nt, (fragment II) to be of interspecific origin.…”
Section: Phylogenetic Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…Mapping of the aligned sequences for break points indicative of recombination with the multiple applications available in RDP-V2 Beta 08 (Martin et al, 2005) and PhylPro version 0.8.1.0 (Weiller, 1998) (each at the default settings) resulted in a similar result for all types of analyses. CHIMAERA (Posada & Crandall, 2001), GENECONV (Sawyer, 1989), MAXCHI (Smith, 1992), RDP (Martin et al, 2005) and PhylPro consistently identified fragments of approximately 1768 nt, between nucleotide coordinates 253 and 2020 (fragment I), and between coordinates 2021 and 2742, about 522 nt, (fragment II) to be of interspecific origin.…”
Section: Phylogenetic Analysismentioning
confidence: 90%
“…Sequence alignments were used to reconstruct phylogenetic trees using the MP option in PAUP* (Swofford, 2002). The aligned sequences were used to identify all putative recombinatorial breakpoints attributable to possible recombination, using RDP2 (Martin et al, 2005), and PhylPro (Weiller, 1998). The default search parameters for scanning the aligned sequences for recombination were implemented, and the highest acceptable probability (P value) was set for RDP2 at 0.001.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, nucleotide sequence patterns of a number of different haplotypes in a population are used to characterize candidate regions for conversion events which may have taken place in the past. Phylogenetic (Gyllensten et al, 1991), graphical or statistical (Sawyer, 1989 ;Kuhner et al, 1991 ;Betran et al, 1997 ;Weiller, 1998) methods are employed. However, it is generally very difficult to reconstruct ancestral haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Takahata (1994) found that, while in some cases significant clustering of nucleotide site configurations across sequences could be detected, such clustering does not imply that conversion has taken place. Weiller (1998) describes a graphical method to detect putative recombination sites in sets of homologous sequences. Betran et al (1997) have suggested a method of estimating the number and length distribution of conversion tracts from DNA sequence data.…”
Section: Introductionmentioning
confidence: 99%
“…Para buscar posibles eventos de recombinación dentro de cada una de estas regiones genómicas se utilizaron los programas PHYLPRO (Weiller, 1998) y GENECONV versión 1.81 (Sawyer, 1989).…”
Section: Análisis De Secuenciasunclassified